Pengaruh Jaminan Sosial Terhadap Motivasi Kerja Karyawan Di Bandar Udara Notohadinegoro Jember Jawa Timur7 - Kifni Yudianto; Miko Tiya Praminto (CV. Multi Kreasi Media, 2022)
The existence of social security for workers as an effort to protect the life of workers in a company has great benefits, therefore as a step to ensure the life of workers, companies really need to include their workforce in the social security program for workers. This study aims to determine influence of social security on employee work motivation at Notohadinegoro Airport Jember and how much influence social security has on employee motivation at Notohadinegoro Airport Jember. This is quantitative research with questioner as the data. Population of this research is employees at Notohadinegoro Airport, Jember. This research used random sampling to 37 respondents. Data analysis used simple linear regression, t test and coefficient of determination test (R2). The results of this study indicate that there is no effect of labor social security on employee work motivation at Jember Notohadinegoro Airport as evidenced by the T-test significance value of 0.987 greater than 0.05. The effect of social security on employee work motivation at Notohadinegoro Airport Jember at 0% further proves that social security does not at all affect the work motivation of employees at Notohadinegoro Airport Jember.